Perbandingan hasil stimulasi ovarium dengan kombinasi klomifen sitrat gonadotropin dan klomifen sitrat pada inseminasi intra uteri - Farida Indriani; Shofwal Widad; Sulchan Sofoewan (JURNAL KESEHATAN REPRODUKSI, 2016)
Background: Infertile couple with the cause of unexplained infertility and male factor can follow intrauterine insemination (IUI) program as a cheap and easy method for infertility therapy. Ovarian stimulation by combination of clomiphene citrate and gonadotropin and also clomiphene citrate alone was done as a superovulation mode to get higher number of mature follicle to gain higher pregnancy rate. Objective : To compare the amount of mature follicles and  endometrial thickness as an outcome of ovarian stimulation between combination drug of clomiphene citrate and gonadotrophin with clomiphene citrate alone.Methods: Observational retrospective cohort. Subject is one cycle intrauterine insemination stimulated either by combination CC gonadotrophin or CC alone, eligible in inclusion criteria and exclusion criteria. Statistic test used was independent t-test, chi-square and logistic regression.Location of study: Infertility Clinic of  Permata Hati, dr. Sardjito Hospital, Yogyakarta.Result: A total of 142 cycle from 98 couples followed IUI and stimulated by combination CC gonadotrophin (n=72) or CC alone (n=70). Multiple mature follicle number was different and statistically significant 77% vs 54%, RR 1,433 (IK95% 1,118-1,836), p=0,005, while endometrial thickness > 7mm was more frequent in combination group but not statistically different with percentage 81,9% vs 74,3%, RR 1,103 (CI95% 0,926-1,315), p=0,367.Conclusion: Ovarian stimulation by combination CC gonadotropin resulting of more multiple mature follicle number while  good endometrial thickness was more in combination group but not statistically significant.Keywords: ovarian stimulation, clomiphene citrate, gonadotrophin, multifollicular, endometrial thickness